Keabsahan Jasa Haji Badal dalam Perspektif Fiqih - Akbar, Muhamad Raf’i; Rafli Mauluddin, Muhammad; Amiruzzidan, Muhammad Rifqi; Mu'is, Ahmad (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2025)
The Hajj pilgrimage is one of the pillars of Islam that must be performed by every Muslim who is capable. Indonesia, being a country with a Muslim-majority population, has a high demand for the Hajj pilgrimage. Consequently, the number of registrants increases significantly each year. The limited quota for Hajj departures results in long waiting periods of up to 19-20 years. This situation has led to the practice of badal hajj, where someone can perform the Hajj on behalf of another person who is unable due to physical limitations, advanced age, or death. This study employs a literature review method to investigate this issue. Badal hajj has strong foundations in Islamic law derived from the Qur'an, Hadith, and scholarly opinions. Its implementation requires several conditions, such as the representative must be a Muslim, of sound mind, mature baligh, legally competent, have previously performed the Hajj for themselves, and represent only one individual per Hajj season. Although badal hajj has become a common practice, it is undeniable that it faces issues, both in its legal basis and practical execution. From a fiqh perspective, differences of opinion persist among Islamic scholars. In practice, various deviations have been committed by irresponsible parties. Therefore, this study also discusses the religious evidence supporting the legal basis of badal hajj, the views of different Islamic schools of thought, and the importance of sincere intentions in performing the pilgrimage. Differences in opinion regarding the eligibility and procedures for badal hajj among scholars emerge as a significant finding requiring further exploration. This research provides a comprehensive understanding of the requirements, conditions, and legal principles of badal hajj to ensure its alignment with Islamic law